Making Alloys (TI1 - xAlx) N using plasma CVD technique from AlCl3 Powder, H2 and N2 Gas ,with solvent TiCl4 - Moto, Keba (Makara Journal of Technology, 2002)
The substitution of Ti atoms by Al atoms in TiN lattice sites to form (Ti1-xAlx)N is clearly demonstrated by the coatings which were deposited on steel substrate and using plasma CVD technique. The presence of Al atoms in TiN lattice site is shown by means of XRD and EDX techniques: lattice parameters decreasing of TiN as the fraction of Al increases (XRD) and precipitation of hexagonal AlN phase (XRD) as the fraction of Al exceeding 0.8 (EDX). The hardness of these coating are just around 30 GPa, which is beyond the values reported in literatures.